تأثير حبوب منع الحمل على الموجودات التنظيرية والخلوية في عنق الرحم - سلمان, صفاء; أحمد, عيسى; شاويش, ميسم (Latakia University Journal -Medical Sciences Series, 2019)
أجري البحث في قسم التوليد وأمراض النساء بمشفى الأسد الجامعي, في الفترة بين 1/5/2010-1/5/2009. شمل البحث 384 مريضة, أجريت لهنّ لطاخة بابانيكولاو وتنظير مكبر لعنق الرحم, للتحري عن تأثير حبوب منع الحمل الفموية على الموجودات التنظيرية والخلوية في عنق الرحم.وتمت مقارنة النتائج لدى المريضات المستخدمات لحبوب منع الحمل (174) مريضة, مع مجموعة الشاهد من المريضات غير المستخدمات لأي من وسائل منع الحمل (210) مريضة. كما تمت دراسة تأثير كل من عوامل الخطورة المتعددة والمعروفة للإصابة بسرطان عنق الرحم على الموجودات التنظيرية لدينا. وتبين لدينا بالمقارنة بين المجموعتين وجود فرق في نسبة الموجودات التنظيرية الشاذة: إذ كانت النسبة في عينة مستخدمات حبوب منع الحمل =16,66%. وفي العينة الشاهد كانت النسبة=11,9%. وهذا يؤكد تأثير موانع الحمل الفموية في زيادة خطورة الإصابة بسرطان عنق الرحم, مع تأكيد ضرورة الكشف الدوري باللطاخة والتنظير. This research was conducted in the Department of Obstetrics and Gynecology at the University Al-Assad Hospital in the period between 1/5/2009—1/5/2010. This study included (384) patients, who submitted to colposcopy and papanicolaou smear to detect the effect of OCPs on colposcopic and cellular findings. The results in OCPs users (174) patients were compared to control group from patients who didn’t use any of contraception (210) patients. The effect of different risk factors relating to cervix cancer on the colposcopic findings had been also studied. We found that there was a difference in the rate of abnormal colposcopic findings. This rate in the OCPs users sample was: 16,66%. In the second was: 11,9 %. This assures that oral contraceptive pills increase the risk of cervical cancer, next to ascertaining the importance of frequent colposcopy and papanicolaou smear test.